2009
DOI: 10.1088/0957-4484/20/12/125608
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature synthesis and characterization of MgO/ZnO composite nanowire arrays

Abstract: Large scale dendritic MgO/ZnO composite nanowire arrays have been successfully synthesized on Si substrates using a two-step sequential hydrothermal synthesis at low temperature for the first time. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), scanning transmission electron microscopy (STEM), and x-ray photoelectron spectroscopy (XPS) were systematically carried out to confirm and elaborate the potentially localized Mg surface alloying process into the ZnO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 29 publications
0
42
1
Order By: Relevance
“…This technique was reported to increase the emission intensity by a few times due to the quantum confi nement effect of the photogenerated carriers in the ZnO cores. [7][8][9][10] In the present paper, we report that sheathing well-faceted MgO nanorods with a semiconductor fi lm with an optimal thickness resulted in ultraintense luminescence characteristic of the sheath material and its origin is discussed. The intensity of the blue-green emission from the MgO-core/TiO 2 -shell nanostructures with a specifi c shell layer thickness ( ≈ 20 nm) was ≈ 220 times higher than that of the original orange emission from the MgO nanorods.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…This technique was reported to increase the emission intensity by a few times due to the quantum confi nement effect of the photogenerated carriers in the ZnO cores. [7][8][9][10] In the present paper, we report that sheathing well-faceted MgO nanorods with a semiconductor fi lm with an optimal thickness resulted in ultraintense luminescence characteristic of the sheath material and its origin is discussed. The intensity of the blue-green emission from the MgO-core/TiO 2 -shell nanostructures with a specifi c shell layer thickness ( ≈ 20 nm) was ≈ 220 times higher than that of the original orange emission from the MgO nanorods.…”
mentioning
confidence: 74%
“…[ 2 , 3 ] The luminescence property of 1D nanostructures can be further enhanced by creating core/shell heterostructures. [4][5][6] Ultraviolet photoluminescence (PL) enhancement by sheathing ZnO 1D nanostructures with a larger bandgap material such as ZnS, [ 7 ] SnO 2 , [ 8 ] MgO, [ 9 ] or Al 2 O 3 [ 10 ] has recently been demonstrated. This technique was reported to increase the emission intensity by a few times due to the quantum confi nement effect of the photogenerated carriers in the ZnO cores.…”
Section: Doi: 101002/adma201004266mentioning
confidence: 99%
“…In their method, common ZnO nanowire arrays were immersed into an aqueous solution of Zn(NO 3 ) 2 ·6H 2 O, HMTA, and Mg(NO 3 ) 2 ·6H 2 O in a 1 : 1 : 2 ratio, at a growth temperature of 155 °C for 4 h. In the photoluminescence spectra, ZnO:MgO nanowires showed a blue-shifted near-band-edge UV emission at both room temperature and low temperature, relative to the pristine ZnO nanowires [265].…”
Section: Alloyingmentioning
confidence: 99%
“…16 Of these techniques, formation of core-shell nanostructures by encapsulating ZnO nanostructures with other semiconducting oxide thin films has been reported by many research groups. [17][18][19][20][21][22][23][24][25][26] Recently, we reported that ultraintense shortwavelength emission could be obtained from ZnO-sheathed MgO nanorods induced by subwavelength optical resonance cavity formation. 27 This technique differs from previous encapsulation techniques in that the core and shell materials were MgO and ZnO, respectively.…”
Section: -12mentioning
confidence: 99%